PEDAGOGICAL MONITORING OF THE DEVELOPMENT OF SOCIAL ACTIVITY OF EDUCATORS OF THE FUTURE PRESCHOOL EDUCATIONAL ORGANIZATION BASED ON DIGITAL TECHNOLOGIES (KONFERENSIYA, 2025)
The article presents the theoretical foundations, goals and objectives of pedagogical monitoring, and justifies the need to integrate computer production into the process of professional and social competences and development. Based on monitoring, ways are shown to correct the quality of cleaning of educators, establish effective feedback in the educational process, and improve the quality of preschool education. According to the research study, personal pedagogical monitoring is an effective mechanism for interpreting socially active, mobile and innovative educators in the modern education system of Uzbekistan.